Towards including soil ecotoxicity of microplastics and tire wear particles into life cycle assessment - Merve Tunali; Bernd Nowack (Ecotoxicology and Environmental Safety)
The presence of microplastics, including tire wear particles, has been documented in various environmental systems, including soils. Despite a lot of research of the effects of microplastics and tire wear particles on individual soil organisms, an evaluation of their overall impact on soil ecosystems is still missing. Thus, it is not possible to assess their complete effects. Life cycle assessment can be used as a tool to fill this gap, however, effect factors which enable quantifying the toxic pressure on soil ecosystems in relation with the pollutant concentration are limited for microplastics and are not available for tire wear particles. As a first step to address this gap, we conducted a hazard assessment and developed a probabilistic species sensitivity distribution (pSSD) for microplastics and tire wear particles, from which the effect factors were derived. The mean hazard concentration at which 20 % of the species were exposed to a concentration above EC10eq was found to be 0.22 g/kg for microplastics and 0.25 g/kg for tire wear particles. The calculated effect factors, which define the change in the potentially affected fraction (PAF) of species, were 0.90 and 1.24 PAF kg/g for microplastics and tire wear particles, respectively. This indicates that tire particles may have a slightly greater effect than microplastics on soil systems. However, it should be noted that studies reporting only highest no observed concentrations (HONEC) were included in the tire wear particle database, while they were excluded from the microplastics database as enough data were available. When comparing their impact on ecosystems, microplastics and tire wear particles appear to exert less toxic pressure on soil ecosystems than on aquatic ecosystems per unit of microplastics and ecosystem volume. Our results enhance understanding of the toxic impact of microplastics and tire wear particles on soil systems and support their integration into life cycle assessment through effect factors which can be combined with fate and exposure factors to obtain the ultimate characterization factors used in life cycle assessment.